Effect of Hospital and Post‐Acute Care Provider Participation in Accountable Care Organizations on Patient Outcomes and Medicare Spending - Agarwal, Divyansh (Health Serv Res, 2018)
OBJECTIVE: To test for differences in patient outcomes when hospital and post‐acute care (PAC) providers participate in accountable care organizations (ACOs). DATA/SETTING: Using Medicare claims, we examined changes in readmission, Medicare spending, and length of stay among patients admitted to ACO‐participating hospitals and PAC providers. DESIGN: We compared changes in outcomes among patients discharged from ACO‐participating hospitals/PACs before and after participation to changes among patients discharged from non‐participating hospitals/PACs over the same time period. RESULTS: Patients discharged from an ACO‐participating hospitals and skilled nursing facilities (SNF) had lower readmission rates (−1.7 percentage points, p‐value = .03) than before ACO participation and non‐participants; and lower per‐discharge Medicare spending (−$940, p‐value = .001), and length of stay (−3.1 days, p‐value <.001) in SNF. Effects among ACO‐participating hospitals without a co‐participating SNF were smaller. Patients discharged from an ACO‐participating hospital and home health agency had lower Medicare per‐discharge spending (−$209; p‐value = .06) and length of stay (−1.6 days, p‐value <.001) for home health compared to before ACO participation and non‐participants. Discharge from an ACO‐participating hospital and inpatient rehabilitation facility did not impact patient outcomes or spending. CONCLUSIONS: Hospital and SNF participation in an ACO was associated with lower readmission rates, Medicare spending on SNF, and SNF length of stay. These results lend support to the ACO payment model.